The Relationship Between Epicardial Adipose Tissue Thickness and Presence of Left Atrial Thrombus in Mitral Stenosis Patients - Ozal,Ender (2020)
Abstract Objective: To examine the relationship between the left atrial (LA) thrombus presence and the epicardial adipose tissue (EAT) thickness. Methods: Three hundred and twelve consecutive rheumatic mitral valve stenosis (RMVS) patients with mitral valve area (MVA) < 2 cm2 were included in this cross-sectional study. Patients were divided into two groups, those with and those without LA thrombus. Routine biochemical analysis and electrocardiographic examinations were carried out. EAT was measured using transthoracic echocardiography. Results: LA thrombus was determined in 84 (26.9%) RMVS patients. In echocardiographic examinations, higher mean gradient and LA diameter as well as lower MVA were found in the group with LA thrombus (P<0.001). In this group, higher C-reactive protein (CRP) and EAT values were also determined (P<0.001). There was significant correlation between EAT and MVA, CRP, LA appendage peak flow velocity, LA anteroposterior diameter, and mean gradient (P<0.001). Higher EAT values were identified as independently associated with the presence of LA thrombus (odds ratio 59.5; 95% confidence interval 12.1-290.10; P<0.001). Conclusion: Transthoracic echocardiography, routinely used in patients with RMVS, can measure EAT to determine patients who are under risk for thrombus.